Photocatalytic induced self-cleaning black@ZnO/CuO super hydrophilic heterojunction modified carbon fiber composite membrane and resource recovery of degreasing wastewater - Wenwen Sun; Li Yin; De Sun; Mingwei Ma; Ao Rong; Guoliang Zhang (Desalination, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Crotiglianoids A−M, tigliane-type diterpenoids from the seeds of Croton tiglium and their anti-hepatic fibrosis activity - Guang-Hai Zhu; Zhen-Zhou Han; Rong Huang; Li-Fen Ma; Xin-Yi Hu; Fei-Yu Zhang; Yi-Ling Liao; Lu Gan; De-an Guo; Wei Li (Phytochemistry, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Synchronously interfacial fire retardancy and mechanical strengthening of glass fiber nylon 6 by temperature-responsive coupling agent - Han Li; Zhi Li; Rong Kuai; Wei-Zheng Zhang; Yanhao Huang; Qing-Wen Zeng; Zhi Hu; De-Yi Wang (Chemical Engineering Journal, 2026)

Effects of Optimized Nitrogen Fertilizer Application on Chlorophyll Fluorescence Characteristics and Dry Matter Accumulation in Sugar Beet - Shi-Feng Dong; Lei Wei; Xing-Bo Tong; Yi-Na Zhang; Rong-Li Jia; Xu-Ming Xing; Shu-De Shi (Sugar Tech, 2025)

O304 is a mitochondrial uncoupler which extends C. elegans lifespan and induces vasorelaxation of rat mesenteric arteries - Wen-Feng Li; Yi Zeng; Yi-Dan Zhang; Rong Zhang; Jing Lang; Wen-Jie Bu; Meng-Ke Zhao; Zhi-Jie Sun; De-Li Dong (Chemico-Biological Interactions, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Vanadium-cobalt oxide nanoflower catalyst for efficient and stable overall water splitting in alkaline and seawater electrolytes - Yong-qi Tian; Song-lin Xu; Jia Li; Shuang-shuang Zhang; Bo-yao Zhang; Rong-da Zhao; Fu-fa Wu; De-peng Zhao (Next Research, 2025)

Improving electrochemical performance of silicon-carbon anode for lithium-ion batteries via one-step etching - Huai-Min Wang; Ying Zhou; Bi-Rong Luo; De-Jun Li; Bo Zhang (Chemical Engineering Journal, 2025)

Low Nitrogen with Split Application Strategy Enhances Antioxidative Defense, Photosynthesis, and Enzymatic Activities to Waxy Maize Under Heat Stress - Song Xu-dong; Ahmad Irshad; Zhang Hui-min; Zhang Zhen-liang; Zhou Guang-fei; Chen Guo-qing; Mao Yu-xiang; Lu Hu-hua; Hao De-rong (Journal of Plant Growth Regulation, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

SIRT3 deficiency reduces PFKFB3-driven T-cell glycolysis and promotes arthritic inflammation - Ting-Ting Wang; Taotao Han; Xinyue Xiao; Dan Guo; Xin Sun; Yudong Liu; Lidan Zhao; Haojie Xu; Rong Li; Lingjuan Jiang; Bo Zhang; Beidi Chen; et al. (Science China Life Sciences, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Origin of the Narenwula quartz vein-type W deposit, Inner Mongolia, China: Insights from geochemistry of hosting granites, fluid inclusions, H-O-S isotopes, and wolframite trace elements - Lin-Wei Wang; De-Hui Zhang; Jia-Jun Liu; Zhu Li; Rong-Zhen Zhang; Xi Diao; Bin Zhang; Guo-Ming Weng (Journal of Asian Earth Sciences, 2024)

Lattice-Engineering modulated band structure facilitates enhanced stability of high-voltage LiCoO2 at 4.6 V - Zhi Zhang; Guang-Xin Wu; Zhou-Liang Tan; He-Zhang Chen; Zhen Yu; Zhen-Rong Yu; Xiao-Bing Huang; Wen-Jie Yang; Ying-De Huang (Chemical Engineering Journal, 2024)

First outbreak of trypanosomiasis in farmed blood parrot cichlids (Vieja melanura♀ × Amphilophus citrinellus♂) from southern China - Jun-Yu (俊余) Zhou (周); Liwen (力文) Xu (徐); Ying-Xin (潆心) Bi (毕); Jinyong (晋勇) Zhang (章); Geoff Hide; De-Hua (德华) Lai (赖); Zhao-Rong (照荣) Lun (伦) (Aquaculture, 2024)

Biodegradation of various grades of polyethylene microplastics by Tenebrio molitor and Tenebrio obscurus larvae: Effects on their physiology - Meng-Qi Ding; Jie Ding; Zhi-Rong Zhang; Mei-Xi Li; Chen-Hao Cui; Ji-Wei Pang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu; Shan-Shan Yang (Journal of Environmental Management, 2024)

hOGG1: A novel mediator in nitrosamine-induced esophageal tumorigenesis - De-Rong Tang; Cheng-Lin Li; Zhi-Yun Xu; Zhen-Zhong Zhang; Qian-Wei Wang; Jian-Qiang Zhao (Food and Chemical Toxicology, 2024)

Shoot Production of Solanum tuberosum L. ‘Yansi’ Using a Simple Continuous Immersion Airlift Bioreactor Culture System - Hang-Lin Song; Rong-de Jin; Xue-Li Quan; Ji-De Zhang; Wen-Wen Qi; Xi-Hua Cui (Potato Research, 2023)

Towards disentangling the classification of freshwater fish trypanosomes - Peng Zhang; Jie Liu; Xiao-Ming Yin; Jun-Yu Zhou; Julius Lukeš; Zhao-Rong Lun; De-Hua Lai (Marine Life Science & Technology, 2023)
Currently, new species of freshwater fish trypanosomes, which are economically important parasites, are being described based on subjectively selected features, i.e., their cell morphology and the host species. We have performed detailed phylogenetic and haplotype diversity analyses of all 18S rRNA genes available for freshwater fish trypanosomes, including the newly obtained sequences of Trypanosoma carassii and Trypanosoma danilewskyi . Based on a sequence similarity of 99.5%, we divide these trypanosomes into 15 operational taxonomic units, and propose three nominal scenarios for distinguishing T. carassii and other aquatic trypanosomes. We find evidences for the existence of a low number of freshwater fish trypanosomes, with T. carassii having the widest geographic and host ranges. Our analyses support the existence of an umbrella complex composed of T. carassii and two sister species.

Catalytic cracking of supercritical n-dodecane over macro-meso-HZSM-5 coatings by vertical secondary growth - Di Rong; Jiaqi Zhang; Hao Li; Wen Guo; De Sun; Zhenheng Diao (Fuel, 2023)

The genomic, transcriptomic, and immunological profiles of perineural invasion in pancreatic ductal adenocarcinoma - Shu-Heng Jiang; Rong-Kun Li; De-Jun Liu; Jun-Li Xue; Min-Hao Yu; Shan Zhang; Li-Min Liu; Jun-Feng Zhang; Rong Hua; Yong-Wei Sun; Xu Wang; Qin Yang; et al. (Science China Life Sciences, 2023)

Urinary phthalate metabolites in pregnant women: occurrences, related factors, and association with maternal hormones - Wei Wu; Zhi-li Ma; Fang Yang; Ping Wu; De-xin Zhang; Rong Zeng; Dan-ling Sun; Liu Cao (Environmental Science and Pollution Research, 2022)

Lignans and phenylpropanoids from the liquid juice of phyllostachys edulis - De-Tao Wang; Ying-Ying Xue; Ying-Fang Zhang; Hang Xun; Qi-Rong Guo; Feng Tang; Jia Sun; Fei-Fei Qi (Natural Product Research, 2021)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Paramyxoviruses respiratory syncytial virus, parainfluenza virus, and human metapneumovirus infection in pediatric hospitalized patients and climate correlation in a subtropical region of southern China: a 7-year survey - Wen-Kuan Liu; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Li Zhang; Shu-Jun Gu; Rong Zhou; Qian Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Association between hyperhomocysteinemia and stroke with atherosclerosis and small artery occlusion depends on homocysteine metabolism-related vitamin levels in Chinese patients with normal renal function - Guan-Hui Wu; Fan-Zhen Kong; Xiao-Feng Dong; De-Feng Wu; Qian-Zhu Guo; Ai-Rong Shen; Qing-Zhang Cheng; Wei-Feng Luo (Metabolic Brain Disease, 2017)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Preparation of Bacterial Cellulose/Inorganic Gel of Bentonite Composite by In Situ Modification - Bo Wang; Gao-xiang Qi; Chao Huang; Xiao-Yan Yang; Hai-Rong Zhang; Jun Luo; Xue-Fang Chen; Lian Xiong; Xin-De Chen (Indian Journal of Microbiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Nucleotide composition bias and codon usage trends of gene populations in Mycoplasma capricolum subsp. capricolum and M. agalactiae - XIAO-XIA MA; YU-PING FENG; JIA-LING BAI; DE-RONG ZHANG; XIN-SHI LIN; ZHONG-REN MA (Journal of Genetics, 2015)

Heme Oxygenase-2 Suppress TNF-α and IL6 Expression via TLR4/MyD88-Dependent Signaling Pathway in Mouse Cerebral Vascular Endothelial Cells - Ren-Jin Chen; Hong-Hua Yuan; Teng-Ye Zhang; Zhen-Zhen Wang; An-kang Hu; Lian-Lian Wu; Zhang-Ping Yang; Yong-Jiang Mao; De-Jun Ji; Xiao-Rong Zhu (Molecular Neurobiology, 2014)

Assessing the real value of farmland in China - Rong Hu; Dao-chi Qiu; De-ti Xie; Xin-ya Wang; Lin Zhang (Journal of Mountain Science, 2014)

Characterization of eubacterial and archaeal community diversity in the pit mud of Chinese Luzhou-flavor liquor by nested PCR–DGGE - Xiao-Fei Ding; Chong-De Wu; Li-Qiang Zhang; Jia Zheng; Rong-Qing Zhou (World Journal of Microbiology and Biotechnology, 2014)

Phylogenic analysis of Chinese Leishmania isolates based on small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA) - Wang Guan; De-Ping Cao; Ke sun; Jia-nan Xu; Jun-rong Zhang; Da-Li Chen; Jian-Ping Chen (Acta Parasitologica, 2012)
The leishmaniases are zoonotic diseases caused by protozoan parasites of the genus Leishmania. Leishmaniases are still endemic in China, especially in the west and northwest froniter regions. To revalue the preliminary phylogenetic results of Chinese Leishmania isolates, we amplified partial fragment of small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA), then tested the phylogenetic relationships among Chinese Leishmania isolates and their relatives by analyzing SSU rRNA gene sequences and 7SL RNA gene sequences. 19 SSU RNA sequences and 9 7SL RNA sequences were obtained in our study, then analyzed with 42 SSU RNA sequences and 32 7SL RNA sequences retrieved from Genbank, respectively. In the Bayesian analysis of the SSU RNA gene, the isolate MHOM/CN/93/GS7 and the isolate IPHL/CN/77/XJ771 are members of Leishmania donovani complex, while the isolate MHOM/CN/84/JS1 clustered with Leishmania tropica. The other 11 Chinese Leishmania isolates (MHOM/CN/90/WC, MCAN/CN/90/SC11, MHOM/CN/80/XJ801, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/ 89/GS5) form an unclassified group, defined as Leishmania sp., and the most relative species to this group is L. tarentolae. In the Bayesian analysis of the 7SL RNA gene, 9 Chinese Leishmania isolates also formed an unclassified group with L. tarentolae, including canine isolate 10, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/ CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/89/GS5. We concluded that: (1) Chinese Leishmania isolates are non-monophyly group; (2) an unclassified group may exist in China, and the most relative species to this group is L. tarentolae; (3) MHOM/CN/84/JS1, which was previously assigned as L. donovani, was most genetically related to L. tropica strain MHOM/SU/74/K27.

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

Molecular phylogenetic reconstruction of Osmanthus Lour. (Oleaceae) and related genera based on three chloroplast intergenic spacers - Shi-Quan Guo; Min Xiong; Chun-Feng Ji; Zhi-Rong Zhang; De-Zhu Li; Zhi-Yong Zhang (Plant Systematics and Evolution, 2011)

Resistin induces rat insulinoma cell RINm5F apoptosis - Chun-lin Gao; De-yu Zhao; Jie Qiu; Chun-mei Zhang; Chen-bo Ji; Xiao-hui Chen; Feng Liu; Xi-rong Guo (Molecular Biology Reports, 2009)

Human Kir2.1 channel carries a transient outward potassium current with inward rectification - De-Yong Zhang; Chu-Pak Lau; Gui-Rong Li (Pflügers Archiv - European Journal of Physiology, 2009)

Quantitative trait loci for carcass traits on pig chromosomes 4, 6, 7, 8 and 13 - Jing Hu Zhang; Yuan Zhu Xiong; Bo Zuo; Ming Gang Lei; Si Wen Jiang; Feng E Li; Rong Zheng; Jia Lian Li; Quan De Xu (Journal of Applied Genetics, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Genetic analysis and breeding use of blast resistance in a japonica rice mutant R917 - Ming Xian Zhang; Jian Long Xu; Rong Ting Luo; De Shi; Zhi Kang Li (Euphytica, 2003)